Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
[tex]\textsf{a)} \quad y=(x+1)^2-4[/tex]
[tex]\textsf{b)} \quad y=2(x-4)^2-2[/tex]
Step-by-step explanation:
Vertex form of a parabola: [tex]y=a(x-h)^2+k[/tex]
(where (h, k) is the vertex and [tex]a[/tex] is some constant)
Part a
- Vertex = (-1, -4)
- Point on parabola = (1, 0)
Substitute the vertex into the formula:
[tex]\begin{aligned}\implies y &=a(x-(-1))^2-4\\y & =a(x+1)^2-4\end{aligned}[/tex]
Substitute the point (1, 0) into the formula:
[tex]\begin{aligned}\implies a(1+1)^2-4&=0\\4a-4&=0\\4a &=4\\a &=1\end{aligned}[/tex]
Therefore, the equation of the parabola in vertex form is:
[tex]y=(x+1)^2-4[/tex]
Part b
- Vertex = (4, -2)
- Point on parabola = (6, 6)
Substitute the vertex into the formula:
[tex]\begin{aligned}\implies y &=a(x-4)^2+(-2)\\y & =a(x-4)^2-2\end{aligned}[/tex]
Substitute the point (6, 6) into the formula:
[tex]\begin{aligned}\implies a(6-4)^2-2&=6\\4a-2 & =6\\4a &=8\\a &=2\end{aligned}[/tex]
Therefore, the equation of the parabola in vertex form is:
[tex]y=2(x-4)^2-2[/tex]
- Vertex at (-1,-4)
- Passes through (1,0)
Find a
- a(x-h)²+k=y
- a(1+1)²-4=0
- 4a-4=0
- 4a=4
- a=1
So
Vertex form
- y=(x+1)²-4
#2
- (h,k)=(4,-2)
- passes through (6,6)
Find a
- a(6-4)²-2=6
- 4a=8
- a=2
Vertex form
- y=2(x-4)²-2
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.